NAQD MATNAL-HADIS BI 'ILMI TARIKH AL-MUTUN (BAHSUN 'AN 'UMRI AS-SAYYIDAH' AISYAH 'INDA NADZHAR AL'AB AL-HABASYAH WA ITTIKHADZ LU'BAH AL-BANAT FI FATH AL-BARI SYARH SAHIH AL-BUKHARI) - Mukhamad Agus Zuhurul Fuqohak (Riwayah: Jurnal Studi Hadis, 2024)
The study of the history of texts is something that is rarely researched in anything other than what relates to the abrogated, even though many commentators of the hadith have placed this study in other areas, so it is worth examining also in a field other than what relates to the abrogated. Indeed, Sheikh Ibn Hajar Al-Asqalani wrote this study in relation to criticizing the statements that Al-Bukhari mentioned in his book, where Al-Asqalani commented on what Al-Bukhari concluded regarding the rulings and others. This study aims to reveal the study of criticism of the tex of hadith with tarikh al-mutun approach conducted by Syekh Ibnu Hajar in the Fath al-Bari Syarh Sahih al-Bukhari. This research using qualitative method, descriptive-analysis and historical philosophical approach founds that tarikh al-mutun can be traced with awwalu ma kadza, qabla, ba’da, and words with nuances of time such as sanata and ‘ama. Syekh Ibnu Hajar uses tarikh al-mutun to trace the real age of ‘Aishah r.a. in the case of the game of the Habashah and its stuffed toys which some scholars claim are not yet mature. However, Ibnu Hajar found the opposite fact. The benefit of the research is to make tarikh al-mutun not only as nasakh-mansukh data, but also useful for critical matn studies as was done by Syekh Ibnu Hajar. This study has been scattered in the books of hadith commentators, such as Sharh al-Nawawi and others, so it must be researched in order to complete this ideal theory.